THE SHARING ECONOMY IS A NEW FORMAT OF SOCIAL INTERACTIONS IN THE 21ST CENTURY - Dudin, Mihail; Shakhov, Oleg; Shakhova, Margarita; Kuznetsova, Elena (Revista Inclusiones, 2019)
Subject/topic. The sharing economy is a new format of social interactions in the 21st century. The subject of the research is the sharing economy (shared consumption) and its development in the 21st century. The paper is aimed at studying the concepts of the modern sharing economy and considering its influence on the formation of a new general consumption model based on empirical analysis. Methods. The following methods were used in this article: empirical, systemic, analytical, economic, and other research methods for the development of the sharing economy (shared consumption) in the 21st century. Results. The article provides the concept of sharing economy (shared consumption). The current state and development of the sharing economy have been analyzed. The types of sharing economies have been characterized. The volumes of sharing economies are increasing rapidly leading to integrated management, which will be as economical as possible. Therefore, within the framework of the sharing economy model, economic agents will independently look for opportunities and contribute to saving resources, materials, energy efficiency, and things like that. Economic and environmental crises are forcing people to find new consumption solutions, and the concept of sharing economy becomes an obvious response in dealing with such processes.